Discourse Markers as Textual Function in Girl Talk: Analysis of Joan Kim's Podcast Episode #16 - Apriliana, Nabila Hani; Silalahi, Pininta Veronika (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
. This research aims to analyze the types and dominant of textual functions in “Girl Talk with Joan Kim Get Real Ep. #16 Podcast on Youtube” with Fraser (1999), Schiffin (1987), and Hyland (2005) as discourse markers theory and classified the textual functions using Brinton (1996) theory of textual functions. A descriptive qualitative method used in this research to help describe data analysis procedure. The researcher found 85 textual functions appear in the “Girl Talk with Joan Kim Get Real Ep.#16 on Youtube” podcast which divided into: Opening markers (6) times, Close frame markers (2) times, Fillers (13) times, Information Indicator (12) times, turn takers (10) times, Topic switcher (2) times, and the most dominant is Repair markers with (25) times appeared. Repair markers commonly used by the hosts because it is a way of expressing state of understanding of information and used to express a change of state for subtle commentary by the hosts suggesting that something is not the most obvious or straightforward interpretation. Keywords: Discourse markers, Discourse analysis, Podcast, Textual functions